Deriving lexical statistics for psycholinguistic research on isiXhosa (Journal of the Digital Humanities Association of Southern Africa (DHASA), 2023)
Psycholinguistic research on isiXhosa and related Bantu languages is scarce. For research on lexical processing in particular, a prerequisite is data on lexical properties that impact word recognition, such as word frequency and neighbourhood density. This paper describes the derivation of these and related lexical statistics from a newly created 4.8-million-word isiXhosa corpus. It then reviews the potential applications of such a lexical database for research on language acquisition, language development, and language processing. The paper closes with recommendations for further work in this domain.
Keywords: isiXhosa; psycholinguistics; lexical processing; corpus; lexical statistics